Age-Related Sparing of Parafoveal Lexical Processing. - Grabbe, Jeremy W.; Allen, Philip A. (Experimental Aging Research)
Background/Study Context: This study examined the role of increased adult age in the processing of lexical information presented in foveal and parafoveal areas of the retina (right and left visual fields). Previous research has shown that older adults are able to compensate for age-related changes though a highly practiced skill (Salthouse, 1984,Journal of Experimental Psychology: General, 113, 345–371). The authors examined if older adults would show a lexical-only parafoveal benefit. Methods: Two experiments were conducted on both younger and older adults. In Experiment 1, participants completed a lexical decision task that presented words in the fovea and parafovea in both visual fields. In Experiment 2, the task was a font discrimination task (nonlexical) with foveal and parafoveal presentation in both visual fields. Results: In Experiment 1, the authors observed word frequency effects for both foveal and right parafoveal presentation locations. This effect was present for both older and younger adults. Experiment 2 was a font discrimination task and there was no right parafoveal advantage for older adults on this task, suggesting that this effect observed in Experiment 1 was lexical in nature due to the highly overlearned nature of word recognition. Conclusion: These results suggest that older adults may compensate for slower encoding time in reading by encoding text to the right of fixation more efficiently than younger adults. This suggests an asymmetrical change in the useful field of view that is lexical in nature.